No Good Deed - Smith , Wesley et al (Simon & Schuster Inc, 2001)
"Save my child. Save Katie".Michael has been taken, kidnapped by a frantic father in a desperate move to save his dying daughter
Keywords: Juvenile literature-Fathers and daughters-Kidnapping-Journalists-Fiction